In Situ Characterization of Biomaterials at Solid‐Liquid Interfaces Using Ellipsometry in the UV‐Visible‐NIR Wavelength Range. Issue 13 (22nd January 2019) - Kalas, Benjamin; Agocs, Emil; Romanenko, Alekszej; Petrik, Peter
Abstract : Understanding interface processes has been gaining crucial importance in many applications of biology, chemistry, and physics. The boundaries of those disciplines had been quickly vanishing in the last decade, as metrologies and the knowledge gained based on their use improved and increased rapidly. Optical techniques such as microscopy, waveguide sensing, or ellipsometry are significant and widely used means of studying solid‐liquid interfaces because the applicability of ions, electrons, or X‐ray radiation is strongly limited for this purpose due to the high absorption in aqueous ambient. Light does not only provide access to the interface making the measurement possible, but utilizing the phase information and the large amount of spectroscopic data, the ellipsometric characterization is also highly sensitive and robust. This article focuses on ellipsometry of biomaterials in the visible wavelength range. The authors discuss the main challenges of measuring thickness and optical properties of ultra‐thin films such as biomolecules. The authors give an overview on different kinds of flow cells from conventional through internal reflection to combined methods. They emphasize that surface nanostructures and evaluation strategies are also crucial parts of in situ bioellipsometry and summarize some of the recent trends showing examples mainly from their research. Abstract : In this Feature Article, the recent results of in situ bioellipsometry are summarized. The usual flowcells for ellipsometric measurements are presented, emphasizing their performance. Advanced techniques for data evaluation, the possibility of combining bioellipsometric measurements with other methods, and the benefits of various surface nanostructures are also discussed.